Damping of electron density Rabi-oscillations and self-induced-transparency in semiconductor quantum dots - Förstner, Jens; Weber, C.; Danckwerts, J.; Knorr, A. (Postconference Digest Quantum Electronics and Laser Science, 2003. QELS.)
A non-Markovian quantum kinetic theory of the coupled electron-phonon system in semiconductor quantum dots is used to analyze the nonlinear dipole decoherence and light propagation dynamics for arbitrary pulse strengths and lengths.
Keywords: tet_topic_qd

Correlated influence of carrier-carrier/carrier-phonon interaction and radiative damping on semiconductor intersubband transitions - Waldmuller, I.; Förstner, Jens; Knorr, A.; Woerner, M.; Reimann, K.; Kaindl, R.A.; Hey, R.; Ploog, K.H. (Postconference Digest Quantum Electronics and Laser Science, 2003. QELS.)
The linewidth of intersubband transitions resulting from simultaneous action of many-body contributions and radiative damping is analyzed. The processes are non-additive and a self-consistent treatment is necessary to explain recent experiments.
Keywords: tet_topic_qw